Sensitivity (Se) and Specificity (Sp) Anthropometric Wall Chart (Awc) Tb/U for Detecting Stunting on Children Aged 6-12 Years - Sudja, Sudja; Sitanggang, Berlin; Shagti, Indhira; Purnawan, Asep I (KnE Life Sciences, 2019)
Anthropometric Wall Chart (AWC) TB/U is a tool developed to screen nutritional status that is easy and fast to use for children aged 6-12 years in the population. The accuracy of the tool in measuring stunting can be seen from its validity. This study aims to get the validity of AWC in 3 (three) cities representing the West (Medan), Central (Bandung) and East (Kupang), Indonesia so that the results could be used for stunting screening of elementary school children wider coverage. The study was conducted in a cross-sectional manner with a sample of 270 elementary students from grade 1 to grade 6 in 3 cities (Medan, Kupang, and Bandung) whose nutritional status was measured by using AWC TB / U and TB / U index using microtoise. The results of the study of the use of AWC in Medan showed that there were 20 (22.2%) stunting children, with Se value of 68.8% and Sp value of 87.8%, PPV 55%, and NPV 92.9%. In Kupang, there were 21 (23.3%) children who were stunting with a value of Se 60.0% and Sp 98.2%, and in Bandung, there were 12 (13.3%) stunted children with Se value of 72.7% and Sp 94.9%. Combined in 3 (three) cities get Se value 66.0% and Sp 93.3%, PPV 73.6% and NPV 90.3%. AWC TB / U can be used as a stunting screening tool for diagnosis with the aim of a high Sp value. For students who are detected stunted, further treatment is needed to overcome their nutritional problems.